Catalytic hydrothermal liquefaction of alkali lignin over activated bio-char supported bimetallic catalyst. (October 2021) - Biswas, Bijoy; Kumar, Avnish; Kaur, Ramandeep; Krishna, Bhavya B.; Bhaskar, Thallada
Graphical abstract: Highlights: Maximum bio-oil yield (72.0 wt%) was obtained with Ni-Co/AC under ethanol solvent. Higher % of phenolic monomer compounds were obtained with bimetallic catalysts. Selectively higher amount of vanillin (36.2%) was found with Co/AC catalyst. Abstract: Carbon-based support catalysts are beneficial on account of low material cost, prominent surface area, and stability at high temperature. In this study, biochar derived activated carbon (AC) supported metal catalysts were tested for hydrothermal liquefaction (HTL) of alkali lignin. Catalytic HTL of alkali lignin was carried out at various temperatures (260 to 300 °C) with varying catalysts quantity (5 to 20 wt%), and solvents (water, ethanol, methanol) for 15 min reaction time. As the reaction temperature increased from 260 to 300 °C, conversion increased from 76.2 to 85.5 wt%. Bimetallic catalyst Ni-Co/AC with ethanol solvent system at 280 °C gave highest bio-oil yield (72.0 wt%). Lignin catalytic depolymerization produces monomer phenolic compounds due to efficient breaking of the lignin macromolecule. Thus, the presence of catalyst and solvent increased the cleavage of β-O-4 bonds resulting in increased selectivity towards vanillin (32.3–36.2%).